2011
DOI: 10.1016/j.jaut.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Fine specificity of antibodies against AQP4: Epitope mapping reveals intracellular epitopes

Abstract: The autoantibody to aquaporin-4 (AQP4) is a marker and a pathogenetic factor in Neuromyelitis Optica (NMO) (Devic's syndrome). Our aim was to identify B-cell antigenic linear epitopes of the AQP4 protein and investigate similarities with other molecules. To this end, we screened sera from 21 patients positive for anti-AQP4 antibodies (study group), from 23 SLE and 23 pSS patients without neurologic involvement (disease controls) and from 28 healthy individuals (normal controls). Eleven peptides, spanning the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 38 publications
5
32
1
3
Order By: Relevance
“…6). Another research group performed an epitope mapping using peptides spanning all intracellular and extracellular (but not transmembrane) parts of AQP4 (63,64). They found that ϳ20% of NMO patients and ϳ10% of MS patients have increased serum IgG reactivities against an intracellular region (AQP4 252-275), which overlaps with the peptide filtered in our study.…”
Section: Figsupporting
confidence: 64%
“…6). Another research group performed an epitope mapping using peptides spanning all intracellular and extracellular (but not transmembrane) parts of AQP4 (63,64). They found that ϳ20% of NMO patients and ϳ10% of MS patients have increased serum IgG reactivities against an intracellular region (AQP4 252-275), which overlaps with the peptide filtered in our study.…”
Section: Figsupporting
confidence: 64%
“…The latter point is supported by the fact that infection of oligodendrocytes and astrocytes during PML has been proposed to be LSTc-independent (53). Antibodies against intracellular and nuclear epitopes are, however, well documented in autoimmune diseases (54), and a recent study showed that the intracellular antibody receptor tripartite motif–containing protein 21 (TRIM21), a ubiquitously expressed E3 ubiquitin ligase, provides a mechanism to protect mice from lethal adenoviral infection through intracellular antibody recognition (55). Hence, JCPyV-specific antibodies may contribute to both extracellular and intracellular mechanisms in PML.…”
Section: Discussionmentioning
confidence: 99%
“…In NMO patients, this T-cell epitope resides at amino acids 281-300 adjacent to the most prominent B-cell linear epitope which resides at amino acids 252-275 (Kampylafka et al, 2011). Because both of these epitopes are intracellular and were not found in any other disease tested, the results suggest that in NMO, contrary to the common belief that only the extracellular epitopes are important for disease progression, some extracellular domains may be also relevant, at least in pointing out antigenic similarities between NMO and RRMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that there may be clinical intermediate types within the spectrum of NMO and MS subsets, prompted us to investigate whether we could detect signs of NMO autoimmunity in typical MS patients. A sensitive ELISA method, recently developed by our group (Kampylafka et al, 2011) to describe the dominant B-cell linear epitopes in NMO-AQP4 positive patients, was employed.…”
Section: Introductionmentioning
confidence: 99%